Research on the livelihood capital and livelihood strategies of resettlement in China’s South-to-North Water Diversion Middle Line Project - Li, Qian; Xu, Yi; Zhao, Xue; Xie, Jiaxiao; Jiao, Tianyi; Su, Zhaoxian (Frontiers in Sustainable Food Systems, 2024)
Resettlement is an important part of water conservancy and hydropower projects, and its development is a proper means of comprehensively promoting rural revitalization. The issue of sustainable livelihoods in resettlement has always attracted significant attention. Based on the traditional sustainable livelihood framework, this paper attempts to incorporate psychological capital and construct a sustainable livelihood index system for resettlement caused by water conservancy and hydropower projects. It also adopts research data from 138 migrant resettlement sites along the middle route of the South to North Water Diversion Project, and employs generalized ordinal logistical models to carry out empirical research on the relationship between migrants' livelihood capital and livelihood strategies. The resultsshow that the values of migrants' capital vary across different types of resettlement sites, and natural capital, physical capital, social capital, psychological capital are greatly affected by location distribution, while human capital and financial capital show only slight differences.The choice of migrants' livelihood strategies also vatu across different resettlement sites, and these strategies are closely related to their livelihood capitals showing a positive correlation.The role played by different kinds of livelihood capitals in the transformation of migrants' livelihood strategies vary, and the impact of migrants' livelihood capital on this transformation also differs. The roles of various livelihood capitals in the transformation of migrants' livelihood strategies are different, and the extents to which each livelihood capital plays a role will change as migrants' livelihood strategies tend to diversify. This study can provide a reference for the formulation, implementation and optimization of policies related to the relocation and resettlement of migrants from water conservancy and hydropower projects, post-completion support and livelihood development.